2007
DOI: 10.1097/0b013e31814da971
|View full text |Cite
|
Sign up to set email alerts
|

Propofol and Methohexital as Anesthetic Agents for Electroconvulsive Therapy

Abstract: Propofol, as compared with methohexital, results in a more moderate increase in blood pressure and shorter seizure duration. The seizure quality did not differ significantly between the 2 groups. We detected a tendency toward improved cognitive performance after anesthesia with propofol as compared with methohexital, but with statistical significance in only 2 cognition trials. Therefore, propofol is a safe and efficacious anesthetic for ECT treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(13 citation statements)
references
References 21 publications
0
10
0
3
Order By: Relevance
“…Study quality was assessed using the Cochrane Collaboration’s Tool for Assessing Risk of Bias 17 concomitantly to eligibility. We identified 71 studies, 14 of which met inclusion criteria for the present investigation 9 10 11 12 25 26 27 28 29 30 31 32 33 34 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study quality was assessed using the Cochrane Collaboration’s Tool for Assessing Risk of Bias 17 concomitantly to eligibility. We identified 71 studies, 14 of which met inclusion criteria for the present investigation 9 10 11 12 25 26 27 28 29 30 31 32 33 34 .…”
Section: Resultsmentioning
confidence: 99%
“…We identified 3 studies comparing the effect of MET administration (n = 86) to PROP (n = 78) on seizure duration 29 32 33 . MET was found to be significantly associated with higher seizure duration compared to PROP (SMD = 1.690, 95% CI 0.286; 3.094, p = 0.018, I2 = 93.150%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When combined with other general anesthetics used in ECT (including methohexital and thiopental), propofol did not damage cognitive function and was even found to provide benefit in this regard compared with the effects of the other anesthetics used alone. 7 , 25 In our previous studies, it was shown that propofol itself had a definite antiamnesic effect when used as the sole anesthetic in ECS. 9 , 14 , 26 In the present study, we further showed that propofol combined with MECS (in group M) could reverse memory impairment to a significantly higher level than was observed in the other two depressed groups without undergoing ECS treatments (groups D and P).…”
Section: Discussionmentioning
confidence: 99%
“…[5] Several anesthetic agents such as methohexital, etomidate, ketamine, enflurane, thiopental and propofol are used for this purpose, but the ideal anesthetic agent for ECT procedures remains unclear. [235678] Propofol is widely used in ECT anesthesia as a reference agent due to characteristics such as rapid onset and emergence from anesthesia, minimal postoperative confusion and a lower incidence of hypertension or tachycardia during induction of anesthesia. However, it produces a dose-dependent decrease in seizure duration.…”
mentioning
confidence: 99%